Contesting Religious Moderation in Digital Media: A Fiqh Muʿāmalah and Maqāṣid al-Sharīʿah Perspective - Miftahul Ulum (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the contestation of religious moderation in digital media from the perspectives of Fiqh Muʿāmalah and Maqāṣid al-Sharīʿah as normative frameworks for developing the ethics of digital interaction. This study employs a normative legal research method using conceptual, statutory, and comparative approaches. The data sources consist of the Qur’an, ḥadīth, classical and contemporary fiqh literature, fatwas, regulations related to digital media, and relevant scholarly publications. The analysis is conducted using a descriptive-analytical approach by integrating the principles of Fiqh Muʿāmalah, including al-aṣl fī al-muʿāmalāt al-ibāḥah, al-ḍarar yuzāl, jalb al-maṣāliḥ wa darʾ al-mafāsid, and al-ʿādah muḥakkamah, with the fundamental objectives of Maqāṣid al-Sharīʿah. The findings reveal that religious moderation in the digital sphere is not merely a theological concept but also a form of muʿāmalah practice that requires honesty, justice, responsibility, and respect for human dignity in public communication. The perspective of Fiqh Muʿāmalah provides an ethical foundation for evaluating the legitimacy of religious narratives based on the degree of public benefit (maṣlaḥah) they promote and the potential harm they may generate. Meanwhile, Maqāṣid al-Sharīʿah reinforces the argument that the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), and social order constitutes fundamental objectives that must be realized within the digital ecosystem.